Pemanfaatan Hasil Pembakaran Limbah Cangkang Kelapa Sawit sebagai Bahan Pengganti Pasir pada Pembuatan Beton Normal - Fauzi Rahman; Fathurrahman Fathurrahman (Media Ilmiah Teknik Sipil, 2017)
In 2015 the total area of oil palm plantations in Kalimantan reached 3.47 million Ha with a production of 8.12 million tons per year. Solid waste is in the form of fresh fruit bunches and palm shells. The result of combustion of oil palm shell waste in the form of boiler crust ash is a waste that has chemical elements SiO2, Al2O3, and CaO, with the content of these compounds can affect the strength of the concrete and can increase its strength. In this study, the quality of the concrete mix planned at 28 days is 23 MPa. Concrete testing included compressive strength tests carried out at 3 days, 7 days, 14 days, 28 days, 42 days and 56 days. Before making concrete samples, the mortar compressive strength is tested first by varying the boiler crust ash content by 0%, 15%, 25%, 35%, and 50% to obtain the optimum mixture. Based on the results of the analysis of compressive strength mortar obtained the optimum mixture of 15% for the manufacture of concrete that will be compared with normal concrete. The compressive strength of concrete with the optimum mixture at 28 days is 24.44 Mpa more than the compressive strength of the 23 Mpa plan. Concrete that has the highest compressive strength occurs at the age of 56 days is concrete with the normal mixture with a compressive strength of 34.44 Mpa higher than the compressive strength of concrete with an optimum mixture of 15% boiler crust ash which is 28.51 MPa.